Impact of Endocrine Disruptors on Neural Tube Development in Mammalian Embryos - Sadiq Salam H. Al-Salih; Ahmed Saleem Abbas; Hussein Kadhim Hussein; Tiba Al Temimi; Yusra Al Nasiri (Journal of Biomedicine and Biochemistry, 2026)
Neural tube defects (NTDs) are severe congenital malformations with multifactorial etiologies, including environmental exposures. This study investigates the effects of prenatal exposure to endocrine-disrupting chemicals (EDCs), specifically bisphenol A (BPA) and phthalates, on neural tube closure in a murine model. Pregnant mice were exposed to low doses of EDCs during critical gestational periods. Morphological assessment and molecular analysis revealed increased incidence of NTDs and dysregulated expression of genes involved in neural patterning. These findings underscore the vulnerability of embryonic development to environmental toxicants and the need for regulatory measures to limit human exposure.